2013
DOI: 10.1186/1471-244x-13-320
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal interplay between negative and positive symptom trajectories in patients under antipsychotic treatment: a post hoc analysis of data from a randomized, 1-year pragmatic trial

Abstract: BackgroundSchizophrenia is a highly heterogeneous disorder with positive and negative symptoms being characteristic manifestations of the disease. While these two symptom domains are usually construed as distinct and orthogonal, little is known about the longitudinal pattern of negative symptoms and their linkage with the positive symptoms. This study assessed the temporal interplay between these two symptom domains and evaluated whether the improvements in these symptoms were inversely correlated or independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…Rather, this conceptualization has led to improved ability to diagnose and treat, to predict and track course of illness, response to treatment, and functional outcomes in affected patients (Chen et al 2013; Mohr et al 2004), and to begin to understand the universality versus specificity of underlying neural abnormalities and genetic alterations in driving clusters of symptoms within and across individuals (Barch and Ceaser 2012). Positive symptoms are often more acute and transient and respond most reliably to anti-psychotic medications (Angrist et al 1980; Chien and Yip 2013; Leucht et al 2009).…”
Section: Symptom Dimensions In Schizophrenia—defining An Illness Specmentioning
confidence: 99%
“…Rather, this conceptualization has led to improved ability to diagnose and treat, to predict and track course of illness, response to treatment, and functional outcomes in affected patients (Chen et al 2013; Mohr et al 2004), and to begin to understand the universality versus specificity of underlying neural abnormalities and genetic alterations in driving clusters of symptoms within and across individuals (Barch and Ceaser 2012). Positive symptoms are often more acute and transient and respond most reliably to anti-psychotic medications (Angrist et al 1980; Chien and Yip 2013; Leucht et al 2009).…”
Section: Symptom Dimensions In Schizophrenia—defining An Illness Specmentioning
confidence: 99%
“…Moreover, grouping individuals into those with persistent negative symptoms and those without might mask the true complexity of individual variation in negative symptom course. Chen et al (2013) found that variation in negative symptom course in a cohort of schizophrenia patients was best modelled by four distinct trajectory classes, characterised by differing levels of negative symptoms at baseline and a distinctive pattern of longitudinal change. It is not yet known whether multiple negative symptoms trajectories are similarly evident in FEP.…”
Section: Introductionmentioning
confidence: 99%
“…More recent literature on response trajectories speaks to the notion of differential treatment response and comes closest to what is observed clinically. [43][44][45][46] At first glance, our proposal to subtype schizophrenia clinically may appear to contradict the recent removal of clinical subtypes in DSM-5 33 ; however, these 2 approaches of clinical subtyping have notable differences. The previous clinical subtypes (paranoid, disorganized, catatonic, undifferentiated, and residual) relied on symptom presentation at a specific point, and symptoms have been known to vary across various phases of the illness; hence it suffered from a lack of diagnostic stability, reliability, and validity.…”
Section: Strengths and Limitationsmentioning
confidence: 81%